Optimization of the Use of Bhabinkamtibmas Counseling Guidance to Prevent the Crime of Abuse of Women and Children in the Jurisdiction of Magelang Polresta - Simanjuntak, Michael Bethrand (Advances in Police Science Research Journal, 2024)
The crime of sexual abuse against women and children is a crime that still haunts children and women. This crime can be fatal both physically and mentally to the victim. The rampant incidence of sexual abuse that occurs in the jurisdiction of Magelang Police Station is a disturbance to public order that is very disturbing for groups of minors and women. The police, who are the guardians of the community, are obliged to maintain public order through the Binmas function by carrying out counseling guidance activities as a form of concrete action to increase public awareness regarding the dangers of sexual abuse against women and children to maintain public order. This study aims to describe the phenomenon of sexual abuse against women and children, describe the role of counseling guidance activities by Bhabinkamtibmas, identify factors that influence counseling guidance activities and examine relevant theories and concepts in preventing criminal acts of sexual abuse against women and children in the jurisdiction of Magelang Resor Police Office. The theories used in this research are Management Theory, Communication Theory, and SWOT Theory. In addition, the concepts used in this study include the Concept of Bhabinkamtibmas, the Concept of Guidance and Counseling on Security and Public Order, and the Concept of Violence Against Women and Children. This study also used a qualitative approach with field research methods through direct data collection from related agencies through interviews, observation, and documentation as well as literature studies combined with validation techniques from data triangulation. The results of this study found that cases of sexual abuse against women and children have increased in the last 3 years. So that the role of Bhabinkamtibmas through counseling guidance activities is expected to increase public awareness to prevent this crime. This research examines the application of management theory by applying POAC and 6M and SWOT analysis based on factual conditions which include information from intelligence on problems, rules and regulations related to activities, organizational resources and internal-external factors.